Mike's mystery - Warner, Gertrude Chandler, 1890-; Gringhuis, Dirk, 1918- (New York : Scholastic Inc., by arrangement with Whitman, 1988)
Henry, Jessie, Benny, and Violet Alden meet Mike Wood and a strange chain of events begins. Mike's house is mysteriously burned down, a man in a blue hat appears, and the Aldens' uranium mine is in danger of being sabotaged.
4.2
3-6
Keywords: Mystery and detective stories; Mystery and detective stories